THE NEED FOR ISLAMIC RELIGIOUS EDUCATION TEACHERS IN SIDOARJO DISTRICT AREAS - Lilik Huriyah; Salma Nabillah; Shavira Nur Rahmawati (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2020)
The ideal ratio between the number of Islamic Religious Education (PAI) teachers and the number of students does not appear to be fulfilled in Sidoarjo district. There are still many schools that lack PAI teachers, although on the other hand there are also some schools that have excess PAI teachers. The purpose of this study was to identify the needs and placement of Islamic Education teachers in schools, as well as to find out various obstacles in the process of meeting the needs and placement of Islamic Education teachers in schools. This study uses a qualitative method. Data collection through observation, interview and documentation techniques. Processing techniques through the stages of editing, coding, tabulating and interpreting data using qualitative descriptive analysis. The results of this study indicate that the high school level requires 9 PAI teachers, while the Vocational High School requires 11 PAI teachers. Various obstacles experienced in the process of placing and fulfilling Islamic Education teachers is the lack of study groups at several schools and the lack of coordination between the education office and the Ministry of Religion.